Wnt4, Wnt6 and β-catenin expression in human placental tissue - is there a link with first trimester miscarriage? Results from a pilot study - Elpiniki Chronopoulou; Vasiliki Koika; Konstantinos Tsiveriotis; Konstantinos Stefanidis; Sotirios Kalogeropoulos; Neoklis Georgopoulos; George Adonakis; Apostolos Kaponis (BMC, 2022)
Abstract Background Demystifying the events around early pregnancy is challenging. A wide network of mediators and signaling cascades orchestrate the processes of implantation and trophoblast proliferation. Dysregulation of these pathways could be implicated in early pregnancy loss. There is accumulating evidence around the role of Wnt pathway in implantation and early pregnancy. The purpose of this study was to explore alterations in the expression of Wnt4, Wnt6 and β-catenin in placental tissue obtained from human first trimester euploid miscarriages versus normally developing early pregnancies. Methods The study group consisted of first trimester miscarriages (early embryonic demises and incomplete miscarriages) and the control group of social terminations of pregnancy (TOPs). The placental mRNA expression of Wnt4, Wnt6 and β-catenin was studied using reverse transcription PCR and real time PCR. Only euploid conceptions were included in the analysis. Results Wnt4 expression was significantly increased in placental tissue from first trimester miscarriages versus controls (p = 0.003). No significant difference was documented in the expression of Wnt6 (p = 0.286) and β-catenin (p = 0.793). There was a 5.1fold increase in Wnt4 expression for early embryonic demises versus TOPs and a 7.6fold increase for incomplete miscarriages versus TOPs - no significant difference between the two subgroups of miscarriage (p = 0.533). Conclusions This is, to our knowledge, the first study demonstrating significant alteration of Wnt4 expression in human placental tissue, from failed early pregnancies compared to normal controls. Undoubtedly, a more profound study is needed to confirm these preliminary findings and explore Wnt mediators as potential targets for strategies to predict and prevent miscarriage.